STUDY ON BIOFILM IN KIWI FRUIT BIOCONTROL - R. M. Fu; F. Yu; Y. Y. Wang; W. L. Chen (Journal of Animal and Plant Sciences, 2015)
This study aims to develop a biofilm with a biocontrol agent to protect kiwifruit against phytopathogenic bacteria. Strain MHT6 was isolated from kiwifruit orchard soil. In vitro assay results showed that the isolated strain effectively suppressed the growth of plant pathogens, such asPseudomonas syringae pv.actinida (PSA) and Pseudomonas syringae pv. Syringae (PSS), which cause kiwifruit canker and leaf blight. Strain MHT6 was identified as Bacillus megaterium through phenotypic, physiological, biochemical, and phylogenetic (16S rDNA) characterization. The strain was mutated under repeated He–Ne laser irradiation to enhance its antagonistic capability. Six mutants were screened, among which mutant MHT67 showed the strongest antagonist capability against PSAand PSS. Mutant MHT67 also demonstrated hereditary stability even after 50 generations. Finally, a biofilm with the biocontrol agent MHT6 was produced and used to protect kiwifruit against phytopathogenic bacteria.
Keywords: Kiwifruit; Bacillus megaterium; He–Ne laser; Mutation; Biofilm